2010
DOI: 10.1111/j.1601-5037.2010.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

CO2 laser‐assisted treatment of a giant pyogenic granuloma of the gingiva

Abstract: This report describes an oral complication during pregnancy for which surgical excision of a PG after delivery seemed the best treatment. It is possible that gender-specific periodontal disease risk factors contributed to the development of the lesion. This is another reason why pregnant women should be encouraged to be assessed by oral health professionals before late pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 19 publications
1
26
0
3
Order By: Relevance
“…Pregnancy tumors are generally observed after first trimester 15,17,18 . Many published case studies have been reported on the observation of pregnancy tumors show that it can be seen in the third trimester likewise 2,3,19 . The relationship between sex hormones and gingivitis in pregnants were reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pregnancy tumors are generally observed after first trimester 15,17,18 . Many published case studies have been reported on the observation of pregnancy tumors show that it can be seen in the third trimester likewise 2,3,19 . The relationship between sex hormones and gingivitis in pregnants were reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Operation during pregnancy is not a preferred therapy method since it shows recurrency. If there is excess bleeding an chewing disorders that disturb patients comfort and daily life surgical tretment can be taken into concideration as shown in some studies 2,17,19 . In over study we didn't consider surgical treatment because the patient stated that she did not have the complaints that we mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations